UPAYA PEMERINTAH NAGARI DALAM MENGATASI PERGAULAN BEBAS (STUDI KASUS PERILAKU BERPACARAN DI NAGARI KOTO BANGUN KECAMATAN KAPUR IX KABUPATEN LIMA PULUH KOTA) - Pratiwi, Novita Sari; Sri, Rahmadani; Erningsih, Erningsih (Universitas Tanjungpura, 2022)
This research is motivated by the promiscuity of teenagers at this time has the potential to lead to deviant behavior in terms of socializing. One form of behavior is how to get along with the opposite sex to cause promiscuity in dating such as having premarital sex so that it leads to pregnancy outside of marriage. Of course this is a concern for the nagari government so it is necessary to overcome promiscuity in these teenagers. The purpose of this study is to describe the efforts of the Nagari government in overcoming promiscuity. The approach used in this study is a descriptive qualitative approach. Data collection techniques were carried out by observation, interviews, and documentation studies. The unit of analysis in this study is the family. The data analysis technique used is the Miles and Huberman model, namely data collection, data reduction, data presentation, and drawing conclusions. The conclusion of this study is than in overcoming the association of teenagers who are increasingly free in terms of dating, sunch as by conducting socialization and counseling in every school in Koto bangun, then giving advice to teenagers who are found dating in a place which is quiet, giving a warning and a sanction if the teenager who has been given advice still reperats it, namely by notifying the parent at home and will process it at the nagari office of they have deviaded outside the limits. But by doing several ways to overcome this, there are still teenagers eho do deviant behavior, especially in terms of dating. So this is certainly a common concern for both parents at home, the community, and the nagari government.